Effectiveness of Platelet-Rich Plasma for Patients With Carpal Tunnel Syndrome: A Systematic Review and meta-Analysis of Current Evidence in Randomized Controlled Trials - Jiang, Jiabao; Xing, Fei; Luo, Rong; Liu, Ming (Frontiers in Pharmacology, 2022)
Background: Recently, there was a series of clinical studies focusing on local injection of platelet-rich plasma (PRP) for treatment of patients with carpal tunnel syndrome (CTS). However, the safety and efficacy of PRP in these CTS patients remains controversial. Therefore, we performed a systematic review to compare PRP with other conservative treatment in treatment of CTS patients. Methods: We systematically searched from electronic databases (Cochrane, PubMed, Web of Science, and EMBASE) up to December 10, 2021. The data of clinical results were extracted and analyzed by RevMan Manager 5.4. Results: Finally, eight randomized controlled studies, involving 220 CTS patients undergoing local injection of PRP were enrolled in this systematic review. All enrolled trials were considered to be of high quality. In the short-term efficacy, the PRP group was significantly lower in symptom severity scale (SSS) compared with the control group (MD=-2.00; 95% CI, -3.15 to -0.85; P =0.0007; I2=0%). In the mid-term efficacy, the PRP group was significantly effective than the control group in the visual analogue scale (MD=-0.63; 95% CI, -1.22 to -0.04; P =0.04; I2=61%), SSS (MD=-3.56; 95% CI, -4.93 to -2.18; P <0.00001; I2=0%), functional status scale (MD=-2.29; 95% CI, -3.03 to -1.56; P <0.00001; I2=45%), sensory peak latency (MD=-0.39; 95% CI, -0.58 to -0.19; P =0.0001; I2=0%) and cross-sectional area of median nerve (MD=-0.20; 95% CI, -0.31 to -0.10; P =0.0002; I2=0%). In the mid-long-term efficacy, the PRP group was only significantly lower in SSS compared with the control group (MD=-2.71; 95% CI, -4.33 to -1.10; P =0.001; I2=38%). Conclusion: Local PRP injection is more effective than other conservative treatments in terms of mid-term efficacy in relieving pain, improving wrist function and symptoms, reducing MN swelling, and partially improving electrophysiological indicators. However, the long-term adverse side and consensus on standardization of PRP in CTS patients still need further large-scale trials.